A process for the production of forsterite refractory

CN122916697APending Publication Date: 2026-10-16SHANGNAN JINRUN MINERAL DEVELOPMENT CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611262136.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-19
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

[0003]现有技术中,天然镁橄榄石原料经高温煅烧后并非纯净的目标产物,而是混杂有镁铁矿、磁铁矿及顽火辉石、斜顽辉石等偏硅酸镁物相,这些低熔物相会降低材料的耐火度与高温结构强度;且多采用磷酸二氢铝作为结合剂与镁质骨料配伍,但酸性磷酸盐与碱性氧化镁之间极易发生剧烈反应导致瞬凝,且磷酸盐与骨料反应生成不溶物会引起材料的时效变化,即保存一段时间后施工性能下降乃至失效;此外,现有烧结助剂如硼酸在高温下易挥发损失,难以在烧结全程持续发挥促烧结作用

Benefits of technology

1、本发明中,活化镁橄榄石粉料经硝酸镧与硝酸铈混合溶液掺杂处理后,稀土离子均匀沉积于粉料表面及内部孔隙,经煅烧形成的高活性稀土氧化物能够抑制高温下晶粒异常长大,同时稀土阳离子进入镁橄榄石晶格后有助于降低各轴向热膨胀系数的差异,从而改善了材料的抗热震稳定性;氧氯化锆经沉淀、煅烧后原位生成纳米氧化锆晶粒,在后续磷酸二氢铝水溶液处理过程中与粉料表面形成良好的界面结合,既增强了粉料与结合剂之间的亲和性,又避免了纳米颗粒的团聚失效问题,改善了天然镁橄榄石因低熔物相及热膨胀各向异性导致的耐火度不足与热震开裂,同时为结合剂的均匀分散提供了良好的基底条件。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The application relates to the technical field of refractory materials, in particular to a process for preparing forsterite refractory material, which comprises the following steps: after dry mixing of modified forsterite powder, electric smelting magnesia fine powder and modified boron aluminates sintering aid, wet mixing and granulation are carried out by adding a modified aluminum phosphate chromium binder aqueous solution, then compression molding, drying and high-temperature sintering are carried out, and the forsterite refractory material is prepared; in the application, the modified forsterite powder solves the problems of low sintering activity and weak interface bonding of raw materials; the modified aluminum phosphate chromium binder solves the problems of incompatibility between the binder and the matrix, insufficient strength and poor storage stability; and the modified boron aluminates sintering aid solves the problems of easy volatilization of the sintering aid at high temperature and poor wettability. Through the synergistic matching of the three modified materials, the normal temperature strength, high-temperature bending strength and thermal shock resistance of the forsterite refractory material are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of refractory materials technology, specifically a process for preparing magnesium olivine refractory materials. Background Technology

[0002] Magnesia olivine is a refractory material mainly composed of magnesium oxide and silicon dioxide. It is the most stable refractory phase in the MgO-SiO2 system, with a melting point as high as 1890℃. It does not undergo any crystal form change from room temperature to the melting point and has a stable crystal form. Magnesia olivine refractories have advantages such as high load softening point, strong resistance to Fe2O3 erosion, resistance to high-temperature molten metal and slag erosion, non-hydration, and good chemical and mineralogical stability.

[0003] In existing technologies, natural forsterite raw materials, after high-temperature calcination, are not the pure target product, but rather contain magnesium silicate phases such as magnesia, magnetite, and enstatite and clinoptilolite. These low-melting-point phases reduce the material's refractoriness and high-temperature structural strength. Furthermore, aluminum dihydrogen phosphate is often used as a binder in combination with magnesia aggregates, but the acidic phosphate reacts violently with the basic magnesium oxide, leading to flash solidification. The reaction of phosphate with aggregates to form insoluble substances causes aging changes in the material, meaning that its workability decreases or even fails after a period of storage. In addition, existing sintering aids such as boric acid are easily volatilized and lost at high temperatures, making it difficult to continuously promote sintering throughout the entire process. Based on these considerations, this invention provides a process for preparing forsterite refractory materials. Summary of the Invention

[0004] The purpose of this invention is to provide a process for preparing forsterite refractory materials. The forsterite refractory materials prepared by this invention have a high load softening temperature, indicating that the material has strong resistance to deformation at high temperatures, strong grain boundary bonding, high refractoriness, and can withstand higher service temperatures. The high thermal shock resistance value indicates that the thermal expansion coefficients of the various phases inside the material are well matched, and the crack propagation path in the microstructure is long and has many branches, which can effectively absorb and buffer the thermal stress generated by thermal shock without causing macroscopic cracking. The high room temperature compressive strength indicates that the material is fully sintered, has a dense structure, strong interparticle interface bonding, and low porosity, making it less prone to damage or breakage during use and transportation.

[0005] To achieve the above objectives, the present invention provides the following technical solution: a process for preparing magnesium olivine refractory materials, comprising the following steps: S1. Dry mix the modified magnesium olivine powder, fused magnesia fine powder, and modified borosilicate sintering aid for 10-20 minutes to obtain a dry mixture. S2. Add the modified aluminum chromium phosphate binder aqueous solution to the dry mixture, wet mix for 15-30 minutes, then granulate and sieve to obtain the molding mixture; S3. Fill the molding mixture into the mold and press it under a pressure of 100-200MPa to obtain the blank; S4. Dry the billet at 100-120℃ for 12-24 hours, then place it in a high-temperature kiln, raise the temperature to 1500-1600℃, hold it for 2-4 hours, and cool it to room temperature with the furnace to obtain magnesium olivine refractory material.

[0006] Further, the weight parts of the raw materials added in S1 are: 80-95 parts of modified magnesium olivine powder, 5-15 parts of fused magnesia fine powder, and 0.5-2 parts of modified borosilicate sintering aid. The modified aluminum chromium phosphate binder aqueous solution has a mass fraction of 30-40%, and the amount of the modified aluminum chromium phosphate binder aqueous solution added is 9-15% of the dry mixture mass.

[0007] Furthermore, the modified magnesium olivine powder is prepared by treating activated magnesium olivine powder with a mixed solution of lanthanum nitrate and cerium nitrate, zirconium oxychloride, and aluminum dihydrogen phosphate. The modified aluminum chromium phosphate binder aqueous solution is prepared by adding deionized water after aluminum dihydrogen phosphate has been treated with basic magnesium carbonate, nano chromium oxide, and tartaric acid. The modified boroaluminate sintering aid is prepared by treating boric acid with alumina, nano-magnesium oxide, and citric acid.

[0008] Further, the preparation method of the activated magnesium olivine powder is as follows: after crushing and coarsely grinding the magnesium olivine raw material, it is placed in a planetary ball mill and mechanically activated by ball milling at a material-to-ball ratio of 1:3-5 to obtain activated powder; the activated powder is placed in a high-temperature furnace and heated to 900-1100℃ and calcined for 1-2 hours to obtain calcined powder; the calcined powder is immersed in a dilute hydrochloric acid solution with a mass fraction of 4-8%, stirred and acid-washed at room temperature, filtered, washed with deionized water until neutral, and dried to obtain activated magnesium olivine powder.

[0009] Further, activated magnesium olivine powder is dispersed in deionized water, a mixed solution of lanthanum nitrate and cerium nitrate and zirconium oxychloride are added, and after stirring and dispersing, ammonia water is added dropwise to adjust the pH to 8.0-9.0. After stirring and reacting at 60-80℃, the mixture is filtered, dried, and then calcined at 500-600℃ to obtain rare earth nano-zirconia composite modified powder. The rare earth nano-zirconia composite modified powder is immersed in a 10-20% (w / w) aqueous solution of aluminum dihydrogen phosphate, stirred and impregnated, filtered, dried, and then calcined at 700-900℃ to obtain modified magnesium olivine powder.

[0010] Further, the mass ratio of the activated magnesium olivine powder to deionized water is 1:2-4; the molar ratio of lanthanum nitrate to cerium nitrate is 2-3:1; the mass of the mixed solution of lanthanum nitrate and cerium nitrate is 0.5-1.5% of the mass of the activated magnesium olivine powder; the amount of zirconium oxychloride added is 1-3% of the mass of the activated magnesium olivine powder; and the mass ratio of the rare earth nano-zirconia composite modified powder to the aluminum dihydrogen phosphate aqueous solution is 1:1.5-3.

[0011] Further, the preparation method of the modified aluminum chromium phosphate binder aqueous solution is as follows: aluminum dihydrogen phosphate is dissolved in deionized water to prepare a solution with a mass fraction of 30-40%, then basic magnesium carbonate is added, and the mixture is stirred at 70-90℃ to obtain an ion-exchange modified product; nano-chromium oxide is added to the ion-exchange modified product, ultrasonically dispersed, and then stirred at 50-70℃ to obtain a dispersion-enhancing product; tartaric acid is added to the dispersion-enhancing product, and the mixture is stirred at 60-80℃ to obtain a dispersion-enhancing product; after the reaction is completed, deionized water is added to obtain the modified aluminum chromium phosphate binder aqueous solution.

[0012] Furthermore, the mass ratio of basic magnesium carbonate to aluminum dihydrogen phosphate is 1:12-18; the mass ratio of nano-chromium oxide to aluminum dihydrogen phosphate is 1:25-40; and the mass ratio of tartaric acid to aluminum dihydrogen phosphate is 1:20-30.

[0013] Further, the preparation method of the modified boroaluminate sintering aid is as follows: boric acid and alumina are mixed and placed in a high-temperature furnace and heated to 800-1000℃. The mixture is kept at this temperature and melted to generate boroaluminate crystal nuclei. The melt is then poured into deionized water and quenched to obtain a highly active boroaluminate glassy precursor. The boroaluminate glassy precursor is crushed, ball-milled, and dispersed in anhydrous ethanol. Nano-magnesium oxide is added, and the mixture is stirred at 40-60℃ to obtain a surface-modified suspension. Citric acid is added to the surface-modified suspension, and the mixture is stirred at 50-70℃, filtered, and dried at 80-100℃ to obtain the modified boroaluminate sintering aid.

[0014] Further, the mass ratio of boric acid to alumina is 0.5-1.5:1; the mass ratio of the boroaluminate glass precursor to anhydrous ethanol is 1:1.5-3; the mass ratio of nano-magnesium oxide to boric acid is 1:30-50; and the mass ratio of citric acid to boric acid is 1:15-25.

[0015] Compared with the prior art, the beneficial effects of the present invention are: 1. In this invention, after the activated magnesium olivine powder is doped with a mixed solution of lanthanum nitrate and cerium nitrate, rare earth ions are uniformly deposited on the surface and internal pores of the powder. The highly active rare earth oxides formed by calcination can inhibit abnormal grain growth at high temperatures. At the same time, the rare earth cations entering the magnesium olivine lattice help reduce the difference in thermal expansion coefficients in all directions, thereby improving the thermal shock resistance of the material. Zirconium oxychloride is precipitated and calcined to generate nano-zirconia grains in situ. During the subsequent treatment with aluminum dihydrogen phosphate aqueous solution, it forms a good interface bond with the powder surface, which not only enhances the affinity between the powder and the binder, but also avoids the problem of nanoparticle agglomeration failure. This improves the insufficient refractoriness and thermal shock cracking of natural magnesium olivine caused by low-melting-point phases and thermal expansion anisotropy, while providing good substrate conditions for the uniform dispersion of the binder.

[0016] 2. In this invention, the modified aluminum chromium phosphate binder, after being treated with basic magnesium carbonate, forms a magnesium-aluminum composite phosphate structure, which reduces the free acidity of the binder and improves the problem of violent reaction when it comes into contact with the basic magnesium oxide in the magnesium raw material; the nano-chromium oxide is uniformly dispersed in the system and forms a strong bond with the phosphate network, which helps to improve the room temperature strength of the binder after curing; tartaric acid forms a stable chelate protective layer with the metal ions in the system, which can block the erosion of moisture in the air and improve the performance degradation problem caused by moisture absorption of the phosphate binder. Moreover, the tartaric acid can be completely decomposed and volatilized during the sintering process, and will not have a negative impact on the high temperature performance of the product.

[0017] 3. In this invention, boric acid and alumina are melted at high temperature and then quenched to obtain a boroaluminate glass precursor with high reactivity. This precursor has good fluidity and spreading ability at low temperatures and can uniformly coat the surface of powder particles, reducing the sintering activation energy. The interface layer formed by modifying the surface of the glass precursor with nano-magnesium oxide is more similar in chemical composition to the magnesium olivine matrix, which improves the problem of poor compatibility between traditional sintering aids and the matrix. Citric acid forms a protective film on the surface of the modified layer, which helps to prevent the activity of nano-magnesium oxide from decreasing during storage. The three factors work together to improve the problem of high-temperature volatility of boric acid and achieve good sintering at lower temperatures. Detailed Implementation

[0018] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.

[0019] It should be noted that the raw materials used in the following embodiments are all commercially available.

[0020] Example 1: A process for preparing magnesium olivine refractory materials, comprising the following steps: S1. Take modified magnesium olivine powder, fused magnesia fine powder, and modified borosilicate sintering aid, and dry mix them in a mixer for 10 minutes to obtain a dry mix.

[0021] S2. Add the modified aluminum chromium phosphate binder aqueous solution to the dry mixture, continue wet mixing for 15 minutes, granulate and sieve to obtain the molding mixture.

[0022] S3. Fill the molding mixture into the mold and press it under a pressure of 100MPa to obtain the blank.

[0023] S4. The billet is dried at 100℃ for 12 hours, then placed in a high-temperature kiln and heated to 1500℃ at a rate of 3℃ / min. It is held at this temperature for 2 hours and then cooled to room temperature in the kiln to obtain magnesium olivine refractory material.

[0024] The weight parts of the raw materials added to S1 are: 80 parts modified magnesium olivine powder, 5 parts fused magnesia fine powder, and 0.5 parts modified boroaluminate sintering aid.

[0025] The mass fraction of the modified aluminum chromium phosphate binder aqueous solution is 30%, and the amount of the modified aluminum chromium phosphate binder aqueous solution added is 9% of the dry mixture mass.

[0026] Modified magnesium olivine powder is prepared by treating activated magnesium olivine powder with a mixed solution of lanthanum nitrate and cerium nitrate, zirconium oxychloride, and aluminum dihydrogen phosphate.

[0027] The modified aluminum chromium phosphate binder is prepared by adding deionized water after aluminum dihydrogen phosphate has been treated with basic magnesium carbonate, nano chromium oxide, and tartaric acid.

[0028] The modified boroaluminate sintering aid is prepared by treating boric acid with alumina, nano-magnesium oxide, and citric acid.

[0029] The preparation method of activated magnesium olivine powder is as follows: magnesium olivine raw material is crushed and coarsely ground to a particle size ≤1mm, placed in a planetary ball mill, and mechanically activated and ball-milled for 2h at a material-to-ball ratio of 1:3 to obtain activated powder; the activated powder is placed in a high-temperature furnace and heated to 900℃ at a rate of 2℃ / min, and calcined for 1h to obtain calcined powder; the calcined powder is immersed in dilute hydrochloric acid solution, stirred and acid-washed at room temperature for 30min, filtered, washed with deionized water until neutral, and dried to obtain activated magnesium olivine powder.

[0030] The preparation method of modified forsterite powder is as follows: Activated forsterite powder is dispersed in deionized water, a mixed solution of lanthanum nitrate and cerium nitrate, and zirconium oxychloride (ZrOCl2∙8H2O) are added, and the mixture is stirred and dispersed for 30 min. Ammonia water is slowly added dropwise to adjust the pH to 8.0, and the mixture is stirred and reacted at 60℃ for 1 h, so that rare earth ions in the form of hydroxides and zirconium ions in the form of zirconium hydroxide co-precipitate on the surface and pores of the powder. After filtration and drying at 80℃, the powder is calcined at 500℃ for 1 h to crystallize zirconium hydroxide in situ into nano-zirconia grains. Rare earth hydroxides decompose into rare earth oxides to obtain rare earth nano-zirconia composite modified powder. The rare earth nano-zirconia composite modified powder is immersed in a 10% aluminum dihydrogen phosphate solution, stirred and impregnated for 1 hour, filtered, dried at 80℃, and calcined at 700℃ for 1 hour to allow aluminum dihydrogen phosphate to decompose and polymerize in situ on the powder surface to form an aluminum phosphate glass phase. This glass phase undergoes an interfacial bonding reaction with the rare earth oxides and nano-zirconia on the powder surface to form a rare earth, zirconium, aluminum, and phosphorus multi-component composite interfacial layer, thus obtaining modified magnesium olivine powder.

[0031] The mass ratio of activated magnesium olivine powder to deionized water is 1:2, the molar ratio of lanthanum nitrate to cerium nitrate is 2:1, the mass of the mixed solution of lanthanum nitrate and cerium nitrate is 0.5% of the mass of activated magnesium olivine powder, and the amount of zirconium oxychloride added is 1% of the mass of activated magnesium olivine powder; the mass ratio of rare earth nano-zirconia composite modified powder to aluminum dihydrogen phosphate aqueous solution is 1:1.5.

[0032] The preparation method of the modified aluminum phosphate chromium binder aqueous solution is as follows: aluminum dihydrogen phosphate is dissolved in deionized water to prepare a 30% (w / w) solution, basic magnesium carbonate is added, and the mixture is stirred at 70°C for 2 hours to allow Mg to form a chromium-containing binder. 2+ Partially replaces H in aluminum dihydrogen phosphate + Magnesium-aluminum composite phosphate was formed, yielding an ion-exchange modified product. Nano-chromium oxide (Cr2O3) was added to the ion-exchange modified product, ultrasonically dispersed for 30 min, and stirred at 50℃ for 1 h to ensure uniform dispersion of the nano-chromium oxide particles in the modified phosphate system. The chromium ions on the surface of the nano-chromium oxide formed coordination bonds with the oxygen atoms in the phosphate group, forming a Cr-OP chemical anchoring structure, firmly anchoring the nanoparticles within the phosphate network framework, yielding a dispersion-enhanced product. Tartaric acid was added to the dispersion-enhanced product, and stirred at 60℃ for 30 min to allow the tartaric acid to react with the Mg in the system. 2+ Al 3+ Cr 3+ A multi-component chelation coordination reaction occurs, forming a stable tartaric acid metal ion chelate. After the reaction is complete, deionized water is added to prepare a modified aluminum chromium phosphate binder aqueous solution.

[0033] The mass ratio of basic magnesium carbonate to aluminum dihydrogen phosphate is 1:12; the mass ratio of nano-chromium oxide to aluminum dihydrogen phosphate is 1:25; and the mass ratio of tartaric acid to aluminum dihydrogen phosphate is 1:20.

[0034] The preparation method of modified boroaluminate sintering aid is as follows: Boric acid (H3BO3) and alumina (Al2O3) are mixed evenly and placed in a high-temperature furnace. The temperature is increased to 800℃ at a rate of 5℃ / min, and the mixture is kept at this temperature for 1 hour to allow the boric acid to dehydrate and react with the alumina in a solid-phase reaction to form boroaluminate (Al2O3). 18 B4O 33 The crystal nuclei were extracted, and the melt was then quenched in deionized water to obtain a highly active boroaluminate glassy precursor. The boroaluminate glassy precursor was crushed, ball-milled to a particle size ≤10μm, dispersed in anhydrous ethanol, and nano-magnesium oxide was added. The mixture was stirred at 40℃ for 1h. The Mg on the surface of the nano-magnesium oxide... 2+ Surface coordination reactions occur with the BO and Al-O bonds on the surface of the boroaluminate glass phase, forming Mg-OB and Mg-O-Al surface bonding layers, thus achieving surface reactive modification of the boroaluminate particles and obtaining a surface-modified suspension. Citric acid is added to the surface-modified suspension, and the mixture is stirred at 50°C for 30 min to allow the citric acid to react with the Mg bonds on the particle surface. 2+ Al 3+ A surface coordination chelation reaction occurs, forming a citric acid-metal coordination protective layer on the surface of the modified layer. After filtration and drying at 80°C, the modified borosilicate sintering aid is obtained.

[0035] The mass ratio of boric acid to alumina is 0.5:1; the mass ratio of boroaluminate glass precursor to anhydrous ethanol is 1:1.5; the mass ratio of nano-magnesium oxide to boric acid is 1:30; and the mass ratio of citric acid to boric acid is 1:15.

[0036] Example 2: A process for preparing magnesium olivine refractory materials, comprising the following steps: S1. Take modified magnesium olivine powder, fused magnesia fine powder, and modified borosilicate sintering aid, and dry mix them in a mixer for 15 minutes to obtain a dry mix.

[0037] S2. Add the modified aluminum chromium phosphate binder aqueous solution to the dry mixture, continue wet mixing for 22 minutes, granulate and sieve to obtain the molding mixture.

[0038] S3. Fill the molding mixture into the mold and press it under a pressure of 150MPa to obtain the blank.

[0039] S4. The billet is dried at 110℃ for 18 hours, then placed in a high-temperature kiln and heated to 1550℃ at a rate of 4℃ / min. It is held at this temperature for 3 hours and then cooled to room temperature in the kiln to obtain magnesium olivine refractory material.

[0040] The weight parts of the raw materials added to S1 are: 87.5 parts of modified magnesium olivine powder, 10 parts of fused magnesia fine powder, and 1.2 parts of modified borosilicate sintering aid.

[0041] The mass fraction of the modified aluminum chromium phosphate binder aqueous solution is 35%, and the amount of modified aluminum chromium phosphate binder aqueous solution added is 12% of the total mass of the dry mixture.

[0042] Modified magnesium olivine powder is prepared by treating activated magnesium olivine powder with a mixed solution of lanthanum nitrate and cerium nitrate, zirconium oxychloride, and aluminum dihydrogen phosphate.

[0043] The modified aluminum chromium phosphate binder is prepared by adding deionized water after aluminum dihydrogen phosphate has been treated with basic magnesium carbonate, nano chromium oxide, and tartaric acid.

[0044] The modified boroaluminate sintering aid is prepared by treating boric acid with alumina, nano-magnesium oxide, and citric acid.

[0045] The preparation method of activated magnesium olivine powder is as follows: magnesium olivine raw material is crushed and coarsely ground to a particle size ≤1mm, placed in a planetary ball mill, and mechanically activated by ball milling at a material-to-ball ratio of 1:4 for 3 hours to obtain activated powder; the activated powder is placed in a high-temperature furnace and heated to 1000℃ at a rate of 3℃ / min, and calcined for 1.5 hours to obtain calcined powder; the calcined powder is immersed in dilute hydrochloric acid solution, stirred and acid-washed at room temperature for 45 minutes, filtered, washed with deionized water until neutral, and dried to obtain activated magnesium olivine powder.

[0046] The preparation method of modified forsterite powder is as follows: Activated forsterite powder is dispersed in deionized water, a mixed solution of lanthanum nitrate and cerium nitrate, and zirconium oxychloride (ZrOCl2∙8H2O) are added, and the mixture is stirred and dispersed for 45 min. Ammonia water is slowly added dropwise to adjust the pH to 8.5, and the mixture is stirred and reacted at 70℃ for 1.5 h, allowing rare earth ions to co-precipitate as hydroxides and zirconium ions as zirconium hydroxide on the powder surface and in the pores. After filtration and drying at 90℃, the mixture is calcined at 550℃ for 1.5 h to allow zirconium hydroxide to crystallize in situ into nano-zirconia grains. Rare earth hydroxides decompose into rare earth oxides to obtain rare earth nano-zirconia composite modified powder. The rare earth nano-zirconia composite modified powder is immersed in a 15% (w / w) aluminum dihydrogen phosphate solution, stirred and impregnated for 1.5 h, filtered, dried at 90 °C, and then calcined at 800 °C for 1.5 h to allow aluminum dihydrogen phosphate to decompose and polymerize in situ on the powder surface to form an aluminophosphate glass phase. This glass phase undergoes an interfacial bonding reaction with the rare earth oxides and nano-zirconia on the powder surface to form a rare earth, zirconium, aluminum, and phosphorus multi-component composite interfacial layer, thus obtaining modified magnesium olivine powder.

[0047] The mass ratio of activated magnesium olivine powder to deionized water is 1:3, the molar ratio of lanthanum nitrate to cerium nitrate is 2.5:1, the mass of the mixed solution of lanthanum nitrate and cerium nitrate is 1.0% of the mass of activated magnesium olivine powder, and the amount of zirconium oxychloride added is 2% of the mass of activated magnesium olivine powder; the mass ratio of rare earth nano-zirconia composite modified powder to aluminum dihydrogen phosphate aqueous solution is 1:2.2.

[0048] The preparation method of the modified aluminum phosphate chromium binder aqueous solution is as follows: aluminum dihydrogen phosphate is dissolved in deionized water to prepare a 35% (w / w) solution, basic magnesium carbonate is added, and the mixture is stirred at 80℃ for 2.5 h to allow Mg to form. 2+ Partially replaces H in aluminum dihydrogen phosphate + Magnesium-aluminum composite phosphate was formed, yielding an ion-substituted modified product. Nano-chromium oxide (Cr2O3) was added to the ion-substituted modified product, ultrasonically dispersed for 45 min, and stirred at 60℃ for 1.5 h to ensure uniform dispersion of the nano-chromium oxide particles in the modified phosphate system. The chromium ions on the surface of the nano-chromium oxide formed coordination bonds with the oxygen atoms in the phosphate group, forming a Cr-OP chemical anchoring structure, firmly anchoring the nanoparticles to the phosphate network framework, yielding a dispersion-enhanced product. Tartaric acid was added to the dispersion-enhanced product, and stirred at 70℃ for 45 min to allow the tartaric acid to react with the Mg in the system. 2+ Al 3+ Cr 3+ A multi-component chelation coordination reaction occurs, forming a stable tartaric acid metal ion chelate. After the reaction is complete, deionized water is added to prepare a modified aluminum chromium phosphate binder aqueous solution.

[0049] The mass ratio of basic magnesium carbonate to aluminum dihydrogen phosphate is 1:15; the mass ratio of nano-chromium oxide to aluminum dihydrogen phosphate is 1:32.5; and the mass ratio of tartaric acid to aluminum dihydrogen phosphate is 1:25.

[0050] The preparation method of modified boroaluminate sintering aid is as follows: Boric acid (H3BO3) and alumina (Al2O3) are mixed evenly and placed in a high-temperature furnace. The temperature is increased to 900℃ at a rate of 7℃ / min, and the mixture is kept at this temperature for 1.5h to melt and react, allowing the boric acid to dehydrate and react with the alumina in a solid-phase reaction to form boroaluminate (Al2O3). 18 B4O 33 The crystal nuclei were extracted, and the melt was then quenched in deionized water to obtain a highly active boroaluminate glassy precursor. The boroaluminate glassy precursor was crushed, ball-milled to a particle size ≤10μm, dispersed in anhydrous ethanol, and nano-magnesium oxide was added. The mixture was stirred at 50℃ for 1.5h. The Mg on the surface of the nano-magnesium oxide... 2+Surface coordination reactions occur with the BO and Al-O bonds on the surface of the boroaluminate glass phase, forming Mg-OB and Mg-O-Al surface bonding layers, thus achieving surface reactive modification of the boroaluminate particles and obtaining a surface-modified suspension. Citric acid is added to the surface-modified suspension, and the mixture is stirred at 60℃ for 45 min to allow the citric acid to react with the Mg bonds on the particle surface. 2+ Al 3+ A surface coordination chelation reaction occurs, forming a citric acid-metal coordination protective layer on the surface of the modified layer. After filtration and drying at 90°C, the modified borosilicate sintering aid is obtained.

[0051] The mass ratio of boric acid to alumina is 1:1; the mass ratio of boroaluminate glass precursor to anhydrous ethanol is 1:2.2; the mass ratio of nano-magnesium oxide to boric acid is 1:40; and the mass ratio of citric acid to boric acid is 1:20.

[0052] Example 3: A process for preparing magnesium olivine refractory materials, comprising the following steps: S1. Take modified magnesium olivine powder, fused magnesia fine powder, and modified borosilicate sintering aid, and dry mix them in a mixer for 20 minutes to obtain a dry mixture.

[0053] S2. Add the modified aluminum chromium phosphate binder aqueous solution to the dry mixture, continue wet mixing for 30 minutes, granulate and sieve to obtain the molding mixture.

[0054] S3. Fill the molding mixture into the mold and press it under a pressure of 200MPa to obtain the blank.

[0055] S4. The billet is dried at 120℃ for 24 hours, then placed in a high-temperature kiln and heated to 1600℃ at a rate of 5℃ / min. It is held at this temperature for 4 hours and then cooled to room temperature in the kiln to obtain magnesium olivine refractory material.

[0056] The weight parts of the raw materials added to S1 are: 95 parts modified magnesium olivine powder, 15 parts fused magnesia fine powder, and 2 parts modified boroaluminate sintering aid.

[0057] The modified aluminum chromium phosphate binder aqueous solution has a mass fraction of 40%, and the amount of modified aluminum chromium phosphate binder aqueous solution added is 15% of the total mass of the dry mixture.

[0058] Modified magnesium olivine powder is prepared by treating activated magnesium olivine powder with a mixed solution of lanthanum nitrate and cerium nitrate, zirconium oxychloride, and aluminum dihydrogen phosphate.

[0059] The modified aluminum chromium phosphate binder is prepared by adding deionized water after aluminum dihydrogen phosphate has been treated with basic magnesium carbonate, nano chromium oxide, and tartaric acid.

[0060] The modified boroaluminate sintering aid is prepared by treating boric acid with alumina, nano-magnesium oxide, and citric acid.

[0061] The preparation method of activated magnesium olivine powder is as follows: magnesium olivine raw material is crushed and coarsely ground to a particle size ≤1mm, placed in a planetary ball mill, and mechanically activated and ball-milled for 4h at a material-to-ball ratio of 1:5 to obtain activated powder; the activated powder is placed in a high-temperature furnace and heated to 1100℃ at a rate of 4℃ / min, and calcined for 2h to obtain calcined powder; the calcined powder is immersed in dilute hydrochloric acid solution, stirred and acid-washed at room temperature for 60min, filtered, washed with deionized water until neutral, and dried to obtain activated magnesium olivine powder.

[0062] The preparation method of modified forsterite powder is as follows: Activated forsterite powder is dispersed in deionized water, a mixed solution of lanthanum nitrate and cerium nitrate, and zirconium oxychloride (ZrOCl2∙8H2O) are added, and the mixture is stirred and dispersed for 60 min. Ammonia water is slowly added dropwise to adjust the pH to 9.0, and the mixture is stirred and reacted at 80℃ for 2 h, so that rare earth ions are co-precipitated in the form of hydroxides and zirconium ions are co-precipitated in the form of zirconium hydroxide on the surface and in the pores of the powder. After filtration and drying at 100℃, the powder is calcined at 600℃ for 2 h to crystallize zirconium hydroxide in situ into nano-zirconia grains. Rare earth hydroxides decompose into rare earth oxides to obtain rare earth nano-zirconia composite modified powder. The rare earth nano-zirconia composite modified powder is immersed in a 20% aluminum dihydrogen phosphate solution, stirred and impregnated for 2 hours, filtered, dried at 100℃, and calcined at 900℃ for 2 hours to allow aluminum dihydrogen phosphate to decompose and polymerize in situ on the powder surface to form an aluminum phosphate glass phase. This glass phase undergoes an interfacial bonding reaction with the rare earth oxides and nano-zirconia on the powder surface to form a rare earth, zirconium, aluminum, and phosphorus multi-component composite interfacial layer, thus obtaining modified magnesium olivine powder.

[0063] The mass ratio of activated magnesium olivine powder to deionized water is 1:4, the molar ratio of lanthanum nitrate to cerium nitrate is 3:1, the mass of the mixed solution of lanthanum nitrate and cerium nitrate is 1.5% of the mass of activated magnesium olivine powder, and the amount of zirconium oxychloride added is 3% of the mass of activated magnesium olivine powder; the mass ratio of rare earth nano-zirconia composite modified powder to aluminum dihydrogen phosphate aqueous solution is 1:3.

[0064] The preparation method of the modified aluminum phosphate chromium binder aqueous solution is as follows: aluminum dihydrogen phosphate is dissolved in deionized water to prepare a 40% (w / w) solution, basic magnesium carbonate is added, and the mixture is stirred at 90℃ for 3 hours to allow Mg to form a chromium-containing binder. 2+ Partially replaces H in aluminum dihydrogen phosphate +Magnesium-aluminum composite phosphate was formed, yielding an ion-exchange modified product. Nano-chromium oxide (Cr2O3) was added to the ion-exchange modified product, ultrasonically dispersed for 60 min, and stirred at 70℃ for 2 h to ensure uniform dispersion of the nano-chromium oxide particles in the modified phosphate system. The chromium ions on the surface of the nano-chromium oxide formed coordination bonds with the oxygen atoms in the phosphate group, forming a Cr-OP chemical anchoring structure, firmly anchoring the nanoparticles within the phosphate network framework, yielding a dispersion-enhanced product. Tartaric acid was added to the dispersion-enhanced product, and stirred at 80℃ for 60 min to allow the tartaric acid to react with the Mg in the system. 2+ Al 3+ Cr 3+ A multi-component chelation coordination reaction occurs, forming a stable tartaric acid metal ion chelate. After the reaction is complete, deionized water is added to prepare a modified aluminum chromium phosphate binder aqueous solution.

[0065] The mass ratio of basic magnesium carbonate to aluminum dihydrogen phosphate is 1:18; the mass ratio of nano-chromium oxide to aluminum dihydrogen phosphate is 1:40; and the mass ratio of tartaric acid to aluminum dihydrogen phosphate is 1:30.

[0066] The preparation method of modified boroaluminate sintering aid is as follows: Boric acid (H3BO3) and alumina (Al2O3) are mixed evenly and placed in a high-temperature furnace. The temperature is increased to 1000℃ at a rate of 10℃ / min, and the mixture is kept at this temperature for 2 hours to allow the boric acid to dehydrate and react with the alumina in a solid-phase reaction to form boroaluminate (Al2O3). 18 B4O 33 The crystal nuclei were extracted, and the melt was then quenched in deionized water to obtain a highly active boroaluminate glassy precursor. The boroaluminate glassy precursor was crushed and ball-milled to a particle size ≤10μm, dispersed in anhydrous ethanol, and nano-magnesium oxide was added. The mixture was stirred at 60℃ for 2 hours. The Mg on the surface of the nano-magnesium oxide... 2+ Surface coordination reactions occur with the BO and Al-O bonds on the surface of the boroaluminate glass phase, forming Mg-OB and Mg-O-Al surface bonding layers, thus achieving surface reactive modification of the boroaluminate particles and obtaining a surface-modified suspension. Citric acid is added to the surface-modified suspension, and the mixture is stirred at 70°C for 60 min to allow the citric acid to react with the Mg bonds on the particle surface. 2+ Al 3+ A surface coordination chelation reaction occurs, forming a citric acid-metal coordination protective layer on the surface of the modified layer. After filtration and drying at 100°C, the modified borosilicate sintering aid is obtained.

[0067] The mass ratio of boric acid to alumina is 1.5:1; the mass ratio of boroaluminate glass precursor to anhydrous ethanol is 1:3; the mass ratio of nano-magnesium oxide to boric acid is 1:50; and the mass ratio of citric acid to boric acid is 1:25.

[0068] Comparative Example 1: The difference between this comparative example and Example 1 is that the modified forsterite powder is replaced with untreated forsterite powder.

[0069] Comparative Example 2 differs from Example 1 in that the modified forsterite powder is replaced with untreated activated forsterite powder.

[0070] Comparative Example 3 differs from Example 1 in that the modified aluminum chromium phosphate binder aqueous solution is replaced with an untreated aluminum dihydrogen phosphate binder aqueous solution.

[0071] Comparative Example 4 differs from Example 1 in that the modified borosilicate sintering aid is replaced with an untreated boric acid sintering aid.

[0072] Performance testing: The relevant properties of the magnesium olivine refractory materials provided in Examples 1 to 3 and Comparative Examples 1 to 4 were tested respectively, and the test data are recorded in Table 1.

[0073] Table 1 - Performance Test Table for Magnesia-Olivine Refractory Materials The load softening temperature of the forsterite refractory materials prepared in Examples 1, 2, 3, 1, 2, 3 and 4 was tested using the test methods in GB / T5989-2023.

[0074] The thermal shock resistance of the forsterite refractory materials prepared in Examples 1, 2, 3, 1, 2, 3 and 4 was tested using the air quenching test method in GB / T30873-2014.

[0075] The room temperature compressive strength of the forsterite refractory materials prepared in Examples 1, 2, 3, 1, 2, 3 and 4 was tested using the test methods in GB / T5072-2023.

[0076] By comparing and analyzing the relevant data in the table, it can be seen that the forsterite refractory material prepared by this invention has a high load softening temperature, indicating that the material has strong resistance to deformation at high temperatures, strong grain boundary bonding, high refractoriness, and can withstand higher service temperatures. The high thermal shock resistance value indicates that the thermal expansion coefficients of the various phases within the material are well matched, and the crack propagation path in the microstructure is long and multi-branched, effectively absorbing and buffering the thermal stress generated by thermal shock without causing macroscopic cracking. The high room temperature compressive strength indicates that the material is fully sintered, has a dense structure, strong interparticle interface bonding, and low porosity, making it less prone to damage or breakage during use and transportation. Therefore, this invention provides a process for preparing forsterite refractory materials with broader market prospects and is more suitable for widespread application.

[0077] The preferred embodiments of the present invention disclosed above are merely illustrative of the invention. These preferred embodiments do not exhaustively describe all details, nor do they limit the invention to the specific implementations described. Clearly, many modifications and variations can be made based on the content of this specification. This specification selects and specifically describes these embodiments to better explain the principles and practical applications of the invention, thereby enabling those skilled in the art to better understand and utilize the invention. The invention is limited only by the claims and their full scope and equivalents.

Claims

1. A process for preparing magnesium olivine refractory materials, characterized in that, Includes the following steps: S1. Dry mix the modified magnesium olivine powder, fused magnesia fine powder, and modified borosilicate sintering aid for 10-20 minutes to obtain a dry mixture. S2. Add the modified aluminum chromium phosphate binder aqueous solution to the dry mixture, wet mix for 15-30 minutes, then granulate and sieve to obtain the molding mixture; S3. Fill the molding mixture into the mold and press it under a pressure of 100-200MPa to obtain the blank; S4. Dry the billet at 100-120℃ for 12-24 hours, then place it in a high-temperature kiln, raise the temperature to 1500-1600℃, hold it for 2-4 hours, and cool it to room temperature with the furnace to obtain magnesium olivine refractory material.

2. The process for preparing magnesium olivine refractory materials according to claim 1, characterized in that, The weight parts of the raw materials added in S1 are: 80-95 parts of modified magnesium olivine powder, 5-15 parts of fused magnesia fine powder, and 0.5-2 parts of modified boroaluminate sintering aid. The modified aluminum chromium phosphate binder aqueous solution has a mass fraction of 30-40%, and the amount of the modified aluminum chromium phosphate binder aqueous solution added is 9-15% of the dry mixture mass.

3. The process for preparing magnesium olivine refractory materials according to claim 1, characterized in that: The modified magnesium olivine powder is prepared by treating activated magnesium olivine powder with a mixed solution of lanthanum nitrate and cerium nitrate, zirconium oxychloride, and aluminum dihydrogen phosphate. The modified aluminum chromium phosphate binder aqueous solution is prepared by adding deionized water after aluminum dihydrogen phosphate has been treated with basic magnesium carbonate, nano chromium oxide, and tartaric acid. The modified boroaluminate sintering aid is prepared by treating boric acid with alumina, nano-magnesium oxide, and citric acid.

4. The process for preparing magnesium olivine refractory materials according to claim 3, characterized in that, The preparation method of the activated magnesium olivine powder is as follows: after crushing and coarse grinding the magnesium olivine raw material, it is placed in a planetary ball mill and mechanically activated by ball milling at a material-to-ball ratio of 1:3-5 to obtain activated powder; the activated powder is placed in a high-temperature furnace and heated to 900-1100℃ and calcined for 1-2 hours to obtain calcined powder; the calcined powder is immersed in a dilute hydrochloric acid solution with a mass fraction of 4-8%, stirred and acid-washed at room temperature, filtered, washed with deionized water until neutral, and dried to obtain activated magnesium olivine powder.

5. The process for preparing magnesium olivine refractory materials according to claim 3, characterized in that, The preparation method of the modified magnesium olivine powder is as follows: the activated magnesium olivine powder is dispersed in deionized water, a mixed solution of lanthanum nitrate and cerium nitrate and zirconium oxychloride are added, the mixture is stirred and dispersed, and ammonia water is added dropwise to adjust the pH to 8.0-9.

0. After stirring and reacting at 60-80℃, the mixture is filtered, dried, and then calcined at 500-600℃ to obtain rare earth nano-zirconia composite modified powder. Rare earth nano-zirconia composite modified powder was immersed in a 10-20% aluminum dihydrogen phosphate aqueous solution, stirred and impregnated, filtered and dried, and then calcined at 700-900℃ to obtain modified magnesium olivine powder.

6. The process for preparing magnesium olivine refractory materials according to claim 5, characterized in that: The mass ratio of activated magnesium olivine powder to deionized water is 1:2-4; the molar ratio of lanthanum nitrate to cerium nitrate is 2-3:1; the mass of the mixed solution of lanthanum nitrate and cerium nitrate is 0.5-1.5% of the mass of activated magnesium olivine powder; the amount of zirconium oxychloride added is 1-3% of the mass of activated magnesium olivine powder; the mass ratio of rare earth nano-zirconia composite modified powder to aluminum dihydrogen phosphate aqueous solution is 1:1.5-3.

7. The process for preparing magnesium olivine refractory materials according to claim 3, characterized in that, The modified aluminum chromium phosphate binder aqueous solution is prepared by dissolving aluminum dihydrogen phosphate in deionized water to prepare a solution with a mass fraction of 30-40%, then adding basic magnesium carbonate, and stirring the reaction at 70-90℃ to obtain the ion-displacement modified product. Nano-chromium oxide was added to the ion-exchange modified product, and after ultrasonic dispersion, the mixture was stirred at 50-70℃ to obtain a dispersion-enhanced product. Tartaric acid was added to the dispersion-enhanced product, and the mixture was stirred at 60-80℃. After the reaction was completed, deionized water was added to obtain an aqueous solution of modified aluminum chromium phosphate binder.

8. The process for preparing magnesium olivine refractory materials according to claim 7, characterized in that: The mass ratio of basic magnesium carbonate to aluminum dihydrogen phosphate is 1:12-18; the mass ratio of nano-chromium oxide to aluminum dihydrogen phosphate is 1:25-40; and the mass ratio of tartaric acid to aluminum dihydrogen phosphate is 1:20-30.

9. The process for preparing magnesium olivine refractory materials according to claim 3, characterized in that, The modified boroaluminate sintering aid is prepared as follows: boric acid and alumina are mixed and placed in a high-temperature furnace and heated to 800-1000℃. The mixture is kept at this temperature and melted to generate boroaluminate crystal nuclei. The melt is then poured into deionized water and quenched to obtain a highly active boroaluminate glassy precursor. The boroaluminate glassy precursor is crushed, ball-milled, and dispersed in anhydrous ethanol. Nano-magnesium oxide is added, and the mixture is stirred at 40-60℃ to obtain a surface-modified suspension. Citric acid is added to the surface-modified suspension, and the mixture is stirred at 50-70℃, filtered, and dried at 80-100℃ to obtain the modified boroaluminate sintering aid.

10. The process for preparing magnesium olivine refractory materials according to claim 9, characterized in that: The mass ratio of boric acid to alumina is 0.5-1.5:1; the mass ratio of the boroaluminate glass precursor to anhydrous ethanol is 1:1.5-3; the mass ratio of nano-magnesium oxide to boric acid is 1:30-50; and the mass ratio of citric acid to boric acid is 1:15-25.